Working Group Discussion on the Ninth Five Year Plan (1997-2002) and Annual Plan 1997-98 Forestry and Wildlife Gujarat State - Planning Commission (Planning Commission, 1997)
Forests play a vital role in environmental conservation. Forests control the soil erosion and increase the moisture retention capacity of the soil. Forests help in checking deterioration of agricultural lands and contribute to a great extent in checking air pollution.
Planning Commission
Planning Commission